2007
DOI: 10.1016/j.jpaa.2005.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Cellular covers of groups

Abstract: In this paper we discuss the concept of cellular cover for groups, especially nilpotent and finite groups. A cellular cover is a group homomorphism c: G → M such that composition with c induces an isomorphism of sets between Hom(G, G) and Hom(G, M). An interesting example is when G is the universal central extension of the perfect group M. This concept originates in algebraic topology and homological algebra, where it is related to the study of localizations of spaces and other objects. As explained below, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 10 publications
1
52
0
Order By: Relevance
“…M be a cellular cover. In previous papers we have noticed that G inherits several important properties from M : First the kernel K D ker c is central in G, that is, G is a central extension of M; and further, if M is nilpotent, then G is nilpotent of the same class; if M is finite then so is G. In addition, we have classified all possible covers of divisible abelian groups ( [CFGS]) and showed that when M is abelian the kernel K is reduced and torsion-free ( [FGS,Theorem 4.7]). The case when M is abelian was independently investigated in [BD] and [D].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…M be a cellular cover. In previous papers we have noticed that G inherits several important properties from M : First the kernel K D ker c is central in G, that is, G is a central extension of M; and further, if M is nilpotent, then G is nilpotent of the same class; if M is finite then so is G. In addition, we have classified all possible covers of divisible abelian groups ( [CFGS]) and showed that when M is abelian the kernel K is reduced and torsion-free ( [FGS,Theorem 4.7]). The case when M is abelian was independently investigated in [BD] and [D].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…In particular, if F ¤ 1, then, since F Ä K, Hom.G; K/ ¤ 0; contradicting [FGS,Lemma 3.5 (c)]. Thus F D 1, so G D G 1 K 2 and hence jGj ġ.…”
Section: Lemma 12 Let K Be a Free Abelian Group Then K Is Weakly-˛mentioning
confidence: 86%
See 1 more Smart Citation
“…We continue the investigations on cellular covers of groups initiated by Farjoun, Göbel and Segev [3], and continued by Chachólski, Farjoun, Göbel and Segev [2] for divisible abelian groups. In this note we consider the case where all the groups are totally ordered abelian groups.…”
Section: Introductionmentioning
confidence: 56%
“…For example the concept, borrowed from topology, of cellular approximation in arbitrary category is a particular case of a colocalization, fact remarked for example in [4]. Some results concerning the cellular approximation may be deduced in a formal, categorical way by stressing this duality.…”
Section: Introductionmentioning
confidence: 99%